Macacos me mordam! Interjeição: uma classe no limbo do sistema lingüístico do português brasileiro - Geovane Fernandes Caixeta (2005)
The present work focuses on the Interjection Phenomenon in the Brazilian Portuguese language. For many years this phenomenon has been considered, according to grammatical compendiums and dictionaries, one of the partes orationis. The proposal of considering the Interjection a word class represents a tacit agreement that deletes the living and e(a)ffective nature of a phenomenon that makes the speaker a particular one in a communicative situation. Starting at the historical point (of the problem) of the Interjection Phenomenon concerning its final position in the partes orationis continuum position that represents the limb where the interjectional manifestation is found aims at showing, in a discursive-functional perspective, which the Interjection Phenomenon is an emotive, expressive and attitudinal demonstration that happens before the interlocutor, situation and message. The speakers relation with these different objects, named Interjective Connections, cam be measured in a scale from the biggest to the smallest involvement. This way, the notion of prototype of interjective manifestations is connected to the expressive involvement of speaker or with all the objects of the Interjective connections [more prototypical] or with some objects [less prototypical] in situations of interlocution. The Interjection Phenomenon is a sign of expressivity and involvement of the speaker in the enunciation.